2019
DOI: 10.31486/toj.18.0002
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Thyroid

Abstract: Background: Primary squamous cell carcinoma of the thyroid (PSCCT) is a rare malignancy of the head and neck, with fewer than 60 cases reported in the literature. We report a case of PSCCT and provide a brief review of the literature. Case Report: A 66-year-old female with a history of a hemithyroidectomy for a benign thyroid lesion presented with 3 months of progressively worsening compressive symptoms and shortness of breath. Physical examination revealed right-sided thyromegaly and right-sided true vocal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
9
1
2
Order By: Relevance
“…PSCCT has been reported to be combined with HT and other thyroid malignancies, 11,13–16 which supports the second theory. However, the origin of most cases, including the remaining PSCCTs in our study and the ones reported in other studies 1,4,17 remains unclear, indicating that the origin of PSCCT requires further investigation.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…PSCCT has been reported to be combined with HT and other thyroid malignancies, 11,13–16 which supports the second theory. However, the origin of most cases, including the remaining PSCCTs in our study and the ones reported in other studies 1,4,17 remains unclear, indicating that the origin of PSCCT requires further investigation.…”
Section: Discussioncontrasting
confidence: 61%
“…The most common clinical symptom was rapid swelling neck, followed by compressive symptoms such as hoarseness, dysphagia and dyspnea, consistent with other studies. 4,18 The mean size of PSCCTs was about 3.87 cm, ranging from 1.0 to 6.0 cm, relatively larger than the average size of general thyroid cancers. 19 This might be due to the aggressive nature of PSCCT and the rapid growth of tumor cells.…”
Section: Discussionmentioning
confidence: 95%
“… 1 Fewer than 60 cases of PSCCT have been reported in the medical literature. 2 PSCCT has been characterized as an extremely aggressive tumor with a poor prognosis, and survival is often shorter than 1 year. 3 The low incidence of PSCCT has impeded clinical research and the development of evidence-based diagnostic algorithms and treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Primary squamous cell carcinoma of the thyroid (ThyPSCC) is a rare thyroid malignancy with high aggressiveness and poor prognosis, comprising ∼0.1-1% of all primary thyroid carcinomas (1)(2)(3)(4)(5)(6). Owing to the rapidly progressing and highly invasive nature of the malignancy, patients with ThyPSCC often present at an advanced stage and are difficult to diagnose in the early stage because of its rare incidence and lack of typical imaging findings (7,8).…”
Section: Introductionmentioning
confidence: 99%